Effects of Magnetic Induction on MHD Boundary Layer Flow of Dusty Fluid a Stretching Sheet - Kimanthi, Mark (My University, 2018)
This research investigates the effects of magnetic field on the MHD boundary layer laminar flow of a dusty fluid over a stretching flat plate surface. The fluid is influenced by an external uniform magnetic field applied perpendicular to the stretching plate. Moreover, the problem studied is characterized by the parameters: Hartmann number, interactions with dust particles, stock resistance, Raynolds number and magnetic Reynolds number. Th basic governing partial differential equations are transformed into a system of ordinary differential equations by applying suitable similarity transformations. These equations are in turn solved numerically by using collocation method through MATLAB fictions bvp4c. These results indicate the possible technological applications of the study in liquid based systems involving stretchable materials such as paint spray in motor vehicles. Although some of the numerical solutions agree with a number of the available results from previous studies, other results differ because of the induced magnetic field introduced in the study.
Keywords: Induced magnetic field; Differential Equations; Dusty Fluid Flow; Skin friction